Indicações geográficas e desenvolvimento territorial: as experiências do Rio Grande do Sul - Dullius, Paulo Roberto (2009)
The new territoriality is, in a geographic area, the socio-cultural interaction determined by present or past affinities, which gives it a distinct identity. Thus, this concept has now become an important subject of study in the social sciences, as well as an object of public policies that aims at designing strategies for development from territorial specificities. Taking into account market environments that offer a very high value differentiated products, these strategies are based on benchmarks of marked quality and able to produce goods that can be recognized in various areas of consumption. For this, the mobilization of social networks seeks to produce and disseminate 'recognition devices'. These are already long-term used in European countries and such devices have gained notoriety recently in Brazil through the granting of Geographical Indication (IG), in two forms: a Statement of Origin (IP) and Designation of Origin (DO). This study aimed to identify the experiences of Geographical Indication recognized in the RS, the IPs of the Valley of the Vineyards and the Pampa Gaúcho in the Southern Campanha, which took key elements in the consolidation of territorial identity manifest in the label indication of origin, contrasting their obstacles, challenges and processes adopted for the achievement and maintenance of the IG and the main impacts arising in their respective territories, with a view to the notion of territorial development. Methodologically, we proceeded with a rescue of material available on secondary sources and visits to the regions in focus for conducting semistructured interviews with key informants. The results were focused on the collection of the general characteristics of each experience, covering their peculiarities and contexts in which they occurred, the difficulties encountered in obtaining the registration of IGs, the most relevant results generated within the territory, and the problems and barriers to current and future maintenance of their IGs, ending with a comparison between the elements found. The experience of IP in the Valley of the Vineyards is nearly a territorial development strategy, since the economic goals led to the creation of a territorial marketing projection abroad, we attract an increasing flow of tourists the place and the social goals led to the (re) construction and promotion of local identity in the local community, to strengthen the sense of community, increase the confidence of the actors on the economic value of local culture, reflecting in large sectors of the territory. Moreover, the experience of IP Pampa Gaúcho da Campanha Meridional seems to have reached sufficient evidence enabling a process of territorial development based on the strategy of the IG, given its character still restricted to the sector in social and within the economic territory. The strategies for using recognition devices can provide the goods, services and agri-food basic territorial competitiveness and greater ability to integrate into differentiated items within the market, it may fulfill the characteristics of segmentation of consumption, as it is presented today, favorably produced to territorial development in the country.